Formulation of Qualification Criteria for Industrial Engineering Graduates as Production Supervisors in the Manufacturing Industry - Rahman Dwi Wahyudi; Evy Herowati; I Made Ronyastra; Jonathan Andersen Irawan (Heuristic, 2025)
The role of a production supervisor in manufacturing operations is a key factor in maintaining quality, stability, and the success of the production process. A production supervisor must maintain process effectiveness, output quality, and daily operational stability. Empirically, the scientific field that aligns with the scope of work of a production supervisor is Industrial Engineering. However, there is still a gap between the competencies of Industrial Engineering graduates and the qualifications required by companies for production supervisor positions. To fill this gap, this article aims to formulate qualification criteria for Industrial Engineering graduates interested in filling Production Supervisor positions in the manufacturing industry. The formulation of qualification criteria is based on job qualifications and requirements data from various types of manufacturers, collected through interviews with human resources department representatives and field observations. The research method used is a survey of experts experienced in the selection and development of human capital. Using the affinity diagram, the job qualifications and requirements are grouped into objective criteria, subjective criteria, and absolute requirements. Then, integrating the Pareto principle with the LINMAP method yields prominent qualification criteria. The results show that companies place the greatest emphasis on subjective qualifications, especially attitude (0,43) and software proficiency (0,43), followed by objective qualifications such as technical knowledge (0,36) and educational background (0,3).  These findings can be a basis for industry in the employee selection process and for universities in designing competency development programs and career preparation for Industrial Engineering students interested in careers as production supervisors.